Overview of Trends in Causes of Pending National Health Insurance Claims for Inpatient Care at Ciamis Regional Hospital - Aulia Fahreza, Salma; Sukawan, Ari (Jurnal Rekam Medis dan Informasi Kesehatan, 2024)
The National Health Insurance (JKN) program in Indonesia aims to provide certainty of comprehensive health insurance for the people. Health financing is obtained through claims to the Social Security Administering Agency (BPJS) Health, which involves the process of submitting and verifying claims. Incomplete claims or claims that do not meet the requirements can result in pending claims, affecting cash flow and health services. This study explores the trend of causes of pending claims at the Ciamis Regional General Hospital in the context of implementing inpatient JKN. By understanding these causes and trends, it is hoped that solutions can be identified to improve the efficiency and sustainability of the JKN program. Descriptive research type. The subjects in this study were three medical record officers and JKN pending claim data for 2023. The method of data collection was through observation using observation sheets, and a calculator to calculate the number of pending files based on administrative aspects, medical aspects, and coding aspects. The causes of pending claims occur due to administrative aspects, medical aspects, and coding aspects. At the Ciamis Regional Hospital, the most cases were due to coding problems, namely errors in coding diseases and actions. Routine communication between teams is established to prevent errors. Factors causing pending claims are administrative aspects, medical aspects, and coding aspects. The most pending errors are due to the coding aspect.